Optimizing WiFi Signal Quality Through Access Point Placement Using Genetic Algorithm Method - Nurmala Dewi Lubis; Novery Lysbetti Marpaung (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
The quality of WiFi signal is one of the critical factors that affects the performance of wireless networks in dense and complex environments. Proper placement of access points (APs) in an area can enhance network coverage and optimize signal quality. However, determining the optimal location for Access Points in a complex environment often presents a complicated and intricate challenge. PT. Globalriau Data Solusi is a company operating in the internet service provider sector. Within this company, there are still several areas with poor signal coverage, which can hinder the work processes of the staff in this office. Therefore, this research aims to optimize the WiFi signal quality by strategically placing Access Points using the Genetic Algorithm (GA) method. This will extend the signal coverage to areas that currently lack proper signal reception and improve the signal quality for overall enhancement. The Genetic Algorithm method proves effective in optimizing WiFi signal quality through the appropriate placement of APs. The results indicate the potential of applying this method in designing and managing efficient and reliable wireless networks in complex environments. This research demonstrates an increase in coverage area from an initial 60% to 80.5%, with signal quality reaching -65 dBm / -45 dBm.